Réinsertion socio-professionnelle des détenus dans les maisons d’arrêt et de correction du Burkina Faso: cas de la Maison d’Arrêt et de Correction de Bobo-Dioulasso (MACB) - Bationo, Bouma Fernand (Criminal justice institutions and the social trajectories of adolescents/youth in Burkina Faso: endogenous/local forms and patterns of punishment, 2021)
According to the International Prison Observatory, prison conditions are generally considered to be poor in every country in the world, although there are notable differences from one country to another. In Burkina Faso, the problem lies in hygiene, snacks and prison overcrowding, which is a major obstacle to the socio-professional integration of inmates, increasing the number of repeat offenders in all the country's prisons. This situation is due to the political, social and economic program governing the prison environment. This raises the question: what are the accompanying measures and the consequences of incarceration conditions on the socio-professional reintegration of prisoners? To answer this question, the present study was carried out at the Bobo-Dioulasso prison (MACB).
Keywords: Administration of Justice; Teenagers; Youth; Punishment; Rehabilitation; Prisons; Correctional institutions; Bobo-Dioulasso